Demonstration of a low-energy on-pathway intermediate in a fast-folding protein by kinetics, protein engineering, and simulation - Jemth, Per (National Academy of Sciences, 2004)
It is controversial whether fast-folding proteins can form productive on-pathway intermediates that are more stable than the denatured state because noncovalent intermediates are usually evanescent. Here, we apply the classical criteria for the existence of intermediates: namely, the intermediates form and react rapidly enough to be on pathway and they can be isolated and characterized. The folding of the 71-residue, mainly α-helical FF domain from human HYPA/FBP11 fulfills these classical criteria, as was found for Im7. The FF domain folds in two phases, one on the μs and the other on the ms time scale. An engineered mutant folds only to a partly folded state, with some 20–40% of the native helical content. The kinetic properties of the mutant are identical to those found for the fast phase of the wild-type protein, and it is likely that the mutant folds just to the intermediate state. A full kinetic analysis of the folding of wild-type protein, using the amplitudes of its native and denatured states and the observed values for the mutant, rules out an off-pathway scheme but fits an on-pathway scheme, with a low energy intermediate that is modeled by the mutant. The experimental proof benchmarks a molecular dynamics method that identifies an obligatory intermediate observed in multiple simulations. The conformational space defining this intermediate is visited several times in the simulations, leading to high populations consistent with the presence of a low energy intermediate.